2020
DOI: 10.1186/s13027-020-00300-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumor aggression among hepatitis-C related hepatocellular carcinoma patients: an observational study regarding the impact of anti-HCV therapy

Abstract: Background: Hepatitis C virus (HCV) represents a major risk factor for hepatocellular carcinoma (HCC) development and anti-HCV therapy is a significant measure to reduce the incidence of HCC, however development of HCC in HCV treated patients is an emerging clinical problem which needs to be investigated. In this study we aim to analyze association between anti-HCV therapy and tumor pattern of HCV related HCC patients. Methods: Hepatocellular Carcinoma (HCC) patients with seropositivity for hepatitis C virus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 70 publications
2
8
2
Order By: Relevance
“…For instance, a recent article by Fayoume et al found that multiplicity and infiltrative patterns were more common in DAAs-treated HCC patients compared to naïve HCC patients (13). Another study revealed that malignant PVT and lymphadenopathy were significantly more frequent in DAAstreated HCC patients (14). On the contrary, we found a more aggressive behavior of HCC among untreated patients from group II compared to group I.…”
Section: Discussioncontrasting
confidence: 55%
“…For instance, a recent article by Fayoume et al found that multiplicity and infiltrative patterns were more common in DAAs-treated HCC patients compared to naïve HCC patients (13). Another study revealed that malignant PVT and lymphadenopathy were significantly more frequent in DAAstreated HCC patients (14). On the contrary, we found a more aggressive behavior of HCC among untreated patients from group II compared to group I.…”
Section: Discussioncontrasting
confidence: 55%
“…Although there are abundant data regarding the HCC occurrence and recurrence after DAAs, few reports assessed the behavior of HCC and access to curative therapy after the DAA treatment (25)(26)(27)(28)(29)(30)(31). Regarding tumor aggression, the patients with HCC in the present study revealed aggression less frequently than those reported in other studies.…”
Section: Discussioncontrasting
confidence: 55%
“…Hepatitis C Virus (HCV) which is a leading cause of chronic liver disease (CLD) and decompensated liver disease (DCLD) affects about 170-200 million individuals worldwide [ 1 ]. In Pakistan, approximately 10 million individuals are infected with HCV and this burden is expected to grow in the coming years [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…These have transformed the treatment of HCV. DAAs have been so successful that sustained viral response (SVR) is achieved in more than 90% of the cases [ 1 ]. However, few studies have linked it to hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation